Regulasi Emosi dan Kelompok Teman Sebaya Pelaku Cyberbullying - Mutia Mawardah; MG Adiyanti (Jurnal Psikologi, 2014)
Technology that is getting more advanced has not only positive but also negative impacts. The number of cyberbullying cases keeps increasing as the use of information technology appliances grows. The subjects of this research were 7th and 8th graders of state junior high school “S”, who were 12-14 years of age and had been using information technologies for at least 2 years. The result of this research showed that peer group conformity and emotional regulation are related to the tendency in them of becoming cyberbulliers as demonstrated by the F value=106.078 and p